2021
DOI: 10.3390/jcm10173953
|View full text |Cite
|
Sign up to set email alerts
|

Guided Bone Regeneration with Concentrated Growth Factor Enriched Bone Graft Matrix (Sticky Bone) vs. Bone-Shell Technique in Horizontal Ridge Augmentation: A Retrospective Study

Abstract: Background: The purpose of this study was to compare clinical results of two different horizontal ridge augmentation techniques: guided bone regeneration with sticky bone (SB) and the bone-shell technique (BS). Methods: Records of patients who underwent horizontal ridge augmentation with SB (test) and BS (control) were screened for inclusion. Pre-operative and 6-month post-operative ridge widths were measured on cone beam computer tomography (CBCT) and compared. Post-operative complications and implant surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…However, edentulous ridge width at implant placement site plays a crucial role: an adequate peri-implant bone envelope has a protective effect against the detrimental influence of the aforementioned factors on peri-implant marginal bone stability. In case of insufficient bone width, the clinician may perform horizontal ridge augmentation procedures [ 20 , 21 ], use implants with reduced diameter [ 22 , 23 ] or plan a combination of the above. Nevertheless, there is no agreement in the literature on the minimum amount of bone that should surround an implant.…”
Section: Introductionmentioning
confidence: 99%
“…However, edentulous ridge width at implant placement site plays a crucial role: an adequate peri-implant bone envelope has a protective effect against the detrimental influence of the aforementioned factors on peri-implant marginal bone stability. In case of insufficient bone width, the clinician may perform horizontal ridge augmentation procedures [ 20 , 21 ], use implants with reduced diameter [ 22 , 23 ] or plan a combination of the above. Nevertheless, there is no agreement in the literature on the minimum amount of bone that should surround an implant.…”
Section: Introductionmentioning
confidence: 99%
“…The results of graft bone density and implant stability after bone grafting with sticky bone were promising. Although the published data are case reports and case series (14,15) the results has shown to be clinically significant compared to xenograft alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study didn't clarify the exact results and the statistical difference at the 3 months follow up time. 15 compared the bone graft with bone shell versus sticky bone around dental implant in 127 implants. The results have shown that the amount of bone formed was comparable in both groups with no statistically significant difference in bone density.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the success of bone augmentation using CBCT has been reported in the literature by others over the past few years. Bone width has been assessed using CBCT for treatments performed with bone blocks, 14,15 and using autogenous bone 16,17 or autogenous tooth roots 18 . Basma and colleagues showed that larger bone particles used during augmentation surgery resulted in a larger increase in bone thickness at the surgical site 19 .…”
Section: Discussionmentioning
confidence: 99%